Costs of Hospitalisation Due to Stroke: Linked Registry and Administrative Clinical Costing Study - Joosup Kim (International Journal of Population Data Science, 2020)
Introduction Routine clinical costing of hospital care provided for a representative sample of patients informs a national price for hospital reimbursement according to the diagnosis related group of a patient. These clinical costing data are available for linkage as part of hospital administrative datasets.